Migration of primordial germline cells is negatively regulated by surrounding somatic cells during early embryogenesis in Drosophila melanogaster - N. V. Dorogova; A. S. Khruscheva; Iu. A. Galimova; D. Yu. Oshchepkov; D. E. Maslov; E. D. Shvedkina; K. A. Akhmetova; S. A. Fedorova (Вавиловский журнал генетики и селекции, 2020)
Cell migration is an important morphogenetic process necessary at different stages of individual development and body functioning. The initiation and maintenance of the cell movement state requires the activation of many factors involved in the regulation of transcription, signal transduction, adhesive interactions, modulation of membranes and the cytoskeleton. However, cell movement depends on the status of both migrating and surrounding cells, interacting with each other during movement. The surrounding cells or cell matrix not only form a substrate for movement, but can also participate in the spatio-temporal regulation of the migration. At present, there is no exact understanding of the genetic mechanisms of this regulation. To determine the role of the cell environment in the regulation of individual cell migration, we studied the migration of primordial germline cells (PGC) during early embryogenesis in Drosophila melanogaster. Normally, PGC are formed at the 3rd stage of embryogenesis at the posterior pole of the embryo. During gastrulation (stages 6–7), PGC as a consolidated cell group passively transfers into the midgut primordium. Further, PGC are individualized, acquire an amoeboid form, and actively move through the midgut epithelium and migrate to the 5–6 abdominal segment of the embryo, where they form paired embryonic gonads. We screened for genes expressed in the epithelium surrounding PGC during early embryogenesis and affecting their migration. We identified the myc, Hph, stat92E, Tre-1, and hop genes, whose RNA interference leads to premature active PGC migration at stages 4–7 of embryogenesis. These genes can be divided into two groups: 1) modulators of JAK/STAT pathway activity inducing PGC migration (stat92E, Tre-1, hop), and 2) myc and Hph involved in epithelial morphogenesis and polarization, i.e. modifying the permeability of the epithelial barrier. Since a depletion of each of these gene products resulted in premature PGC migration, we can conclude that, normally, the somatic environment negatively regulates PGC migration during early Drosophila embryogenesis.